To Probe the Binding Interactions between Two FDA Approved Migraine Drugs (Ubrogepant and Rimegepant) and Calcitonin-Gene Related Peptide Receptor (CGRPR) Using Molecular Dynamics Simulations - Leung, Lauren; Liao, Siyan; Wu, Chun (ACS chemical neuroscience, 2021)
Recently, the FDA approved ubrogepant and rimegepant as oral drugs to treat migraines by targeting the calcitonin-gene related peptide receptor (CGRPR). Unfortunately, there is no high-resolution complex structure with these two drugs; thus the detailed interaction between drugs and the receptor remains elusive. This study uses molecular docking and molecular dynamics simulation to model the drug–receptor complex and analyze their binding interactions at a molecular level. The complex crystal structure (3N7R) of the gepant drugs’ predecessor, olcegepant, was used for our molecular docking of the two drugs and served as a control system. The three systems, with ubrogepant, rimegepant, and crystal olcegepant, were subject to 3 × 1000 ns molecular dynamics simulations and followed by the simulation interaction diagram (SID), structural clustering, and MM-GBSA binding energy analyses. Our MD data revealed that olcegepant binds most strongly to the CGRPR, followed by ubrogepant and then rimegepant, largely due to changes in hydrophobic and electrostatic interactions. The order of our MM-GBSA binding energies of these three compounds is consistent with their experimental IC50 values. SID analysis revealed the pharmacophore of the gepant class to be the dihydroquinazolinone group derivative. Subtle differences in interaction profile have been noted, including interactions with the W74 and W72 residues. The ubrogepant and rimegepant both contact A70 and M42 of the receptor, while olcegepant does not. The results of this study elucidate the interactions in the binding pocket of CGRP receptor and can assist in further development for orally available antagonists of the CGRP receptor.